Memperkuat Eksistensi Pendidikan Islam di Era Revolusi Industri 4.0: Sinergisitas Nilai-Nilai Spiritualisme dalam Pendidikan Islam - Nur Alifah, Nur (Mahad Aly Al Fithrah, 2021)
Without realizing it, education experiences quality imbalance that multidimensional. Based on the phenomenon that continues develop today, there are at least three main reasons; First, education experiences process of reducing meaning, even degraded only memorization activities and skills to do examination (UN). Second, education is plunged into the process of commercialization, where education has turned into a commodity that traded and managed, such as industrial world that tends to be profit oriented. Third, education only express the superiorization of schools, it is schools become increasingly invulnerable, distanced, and suppress students parents, both subtly, and blatantly. This article was written with the aim for study Islamic education, which is then adapted to truth of Islamic teachings. The results talk that in the Industrial Revolution 4.0 era, Islamic education has a very important to formation of morals or morals for humans because with Islamic education lead and direct to physical and spiritual development will be able to form a personality in accordance with the teachings of Islamic religion.